ANALISIS KESTABILAN CABLE STAYED BRIDGE AKIBAT PENGARUH RASIO LEBAR TERHADAP BENTANG JEMBATAN - Sumaiyah Ohorella; Harsoyo Harsoyo (Jurusan Teknik Sipil, Fakultas Teknik Sipil dan Perencanaan, Universitas Islam Indonesia, 2017)
Cable stayed is one of the long spans bridge structure that can minimize the use of pillars so that access under the bridge can be utilized optimally. The main structure of the cable stayed bridge is a cable connected from the bridge deck to the pylon. Problems in long spans bridge structure is wind can provide significant changes in the structure of the bridge. Based on previous experience and research, shows that the influence of wind can cause security and service problems. It can even cause instability in the entire bridge structure due to the flexible nature of its structure. This study aims to analyze the stability of the cable stayed bridge due to the influence of the span ratio to the width of the bridge. The width of the bridge is varied from 14 m to 24 m every 1 m addition modeled using the SAP2000 v.14 program. The object of research using Jembatan Merah Putih, Ambon. The structural response is observed as the natural vibration frequency, internal force and deformation of the structure. The larger the ratio of bridge width to the main span of the bridge, the greater the weight itself and the load of the service work on the bridge structure. So the values of the inner forces that are generated on the main structure include the tower and the bridge deck will be greater for each additional width of the bridge. For the bridge width ratio to bridge span ofÂ 0.093 to 0.133, the width of the bridge 14 m to 22 m remains stable against the aerodynamic effect due to wind according to Leondhart, B â‰¥ L / 30 and still qualifies the maximum deflection according to AASHTOÂ (dmax= ð¿ð‘¡ð‘œð‘¡ð‘Žð‘™/800) and AISC (dmaks= ð¿/150).